Trade reforms and market selection: evidence from manufacturing plants in Colombia - Marcela Eslava Mejía; John Haltiwanger; Adriana D. Kugler; Maurice Kugler (Institute for the Study of Labor (IZA), 2009)
We use plant output and input prices to decompose the profit margin into four parts: productivity, demand shocks, mark-ups and input costs. We find that each of these market fundamentals are important in explaining plant exit. We then use variation across sectors in tariff changes after the Colombian trade reform to assess whether the impact of market fundamentals on plant exit changed with in creased international competition. We find that greater international competition magnifies the impact of productivity, and other market fundamentals, on plant exit. A dynamic simulation that compares the distribution of productivity with and without the trade reform shows that improvements in market selection from trade reform help to weed out the least productive plants and increase average productivity. In addition, we find that trade liberalization increases productivity of incumbent plants and improves the allocation of activity within industries.
urn:nbn:de:101:1-20090720199
Keywords: F43; L25; O47; 330; Trade liberalization; plant exit; market selection; Unternehmensentwicklung; Außenhandelsliberalisierung; Produktivität; Wettbewerb; Konkurs; Verarbeitendes Gewerbe; Kolumbien